2021
DOI: 10.1177/0265407520981152
|View full text |Cite
|
Sign up to set email alerts
|

Are perceptions of grandparenthood related to family and life satisfaction? A study with emerging adults

Abstract: Given the crucial role that grandparents play in the upbringing and well-being of their grandchildren, research regarding the perceived importance of grandparents for their emerging adult grandchildren is of particular relevance. This study examined the relations between perceived grandparents’ roles and family and life satisfaction in Portuguese emerging adults. Participants (N = 387), aged 18–25, completed a structured self-report questionnaire. Findings of structural equation modeling showed that emerging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
(107 reference statements)
2
7
0
Order By: Relevance
“…For participants in both grandparent type groups, parents often set the tone for the grandparent–grandchild relationship by modeling patterns of interaction throughout participants’ lives. This finding aligns with research suggesting family satisfaction acts as a mediator between young adults’ perceived grandparent roles and life satisfaction (Miguel et al, 2021 ) and parents play a critical role in the grandparent–adult grandchild relationship (Monserud, 2011 ).…”
Section: Discussionsupporting
confidence: 89%
“…For participants in both grandparent type groups, parents often set the tone for the grandparent–grandchild relationship by modeling patterns of interaction throughout participants’ lives. This finding aligns with research suggesting family satisfaction acts as a mediator between young adults’ perceived grandparent roles and life satisfaction (Miguel et al, 2021 ) and parents play a critical role in the grandparent–adult grandchild relationship (Monserud, 2011 ).…”
Section: Discussionsupporting
confidence: 89%
“…While grandparents and grandchildren tended to focus their discourse on what foster their emotional closeness, the development of romantic relationships among emerging adults was the only element that was reported as affecting emotional closeness in the relationship, and was systematically initiated by the grandparent. This emotional distance is in line with the norm of non-interference among grandparents (e.g., Kemp, 2004; Monserud, 2011), notwithstanding, we can wonder if it satisfies emerging adults and their grandparents especially as a grandparental support was shown to enhance emerging adults’ life satisfaction (Miguel et al, 2021). Finally, both mentioned the possible pooling of their networks of contacts, giving them both the role of social agent.…”
Section: Discussionmentioning
confidence: 75%
“…These recent findings highlight the well-substantiated influence of gender, both of the grandchild and grandparent, in relational outcomes (e.g., Barnett et al, 2010; MaloneBeach et al, 2018). Miguel et al (2021) also found that considering one’s grandparent to be a counselor and enjoying their grandparental relationships were positively associated with individual and family satisfaction.…”
Section: Introductionmentioning
confidence: 88%
“…In their investigation of “good” grandparenting qualities, MaloneBeach et al (2018) found that university students in the midwestern United States linked the amount of support received in the past and present to grandparent quality. Similarly, grandparental support and advising were perceived as valuable traits by Portuguese university students, though the “advisor” role held more weight for grandsons than granddaughters, who in turn preferred their grandparents to act as “friends” (Miguel et al, 2021). These recent findings highlight the well-substantiated influence of gender, both of the grandchild and grandparent, in relational outcomes (e.g., Barnett et al, 2010; MaloneBeach et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation